Boundary Layer Flow of Jeffrey Fluid over a Stretching Sheet with Convective Boundary Conditions: Application in Polymer Processing - S. M., Zokri; L. A., Aziz; N. S., Arifin; M. K. A., Mohamed; Mohd Zuki, Salleh; Abdul Rahman, Mohd Kasim; N. F., Mohammad (Centre for Advanced Research on Energy (CARe), 2017)
In this study, the boundary layer flow and heat transfer of Jeffrey fluid past a stretching sheet with convective boundary conditions is discussed. The govening system of partial differential equations is transformed into ordinary differential equations, which are then solved numerically via the Keller-box method encoded in MATLAB software. The numerical results for the temperature are obtained for various values of Prandtl. and Biot number. The computation shows that as Prandtl number inereses,. the temperature profile is decreases.